Da Companhia Ford a expansão agrícola de grãos em Belterra/Pa: um estudo sobre os desdobramentos dos processos de desenvolvimento na Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The municipality of Belterra-PA will be the research field of this work that will deal with the development processes triggered in the period from 1934 to 2019, based on two major projects: the implementation of the Ford Project and the Agricultural Expansion of Grains. And, with that, the objective is to analytically describe the developments triggered by these two projects in the municipality, recognizing that such development processes are part of a larger context, the Amazon. The work presented methodologically is bibliographic and qualitative. Initially, the first proposal for a large development project will be presented, the implementation of the Ford Project (from 1934), based on a process of inducing foreign capital in an area of the Amazon region, its origin, implications and completion. Subsequently, the second event is presented, which was the Agricultural Expansion of Grains (mid-1990s), as a means of modifying the structures as a way of developing the place, and many of these changes, as well as the first, were imposed mainly by articulations established by the State. Therefore, the study results in an analytical description of these two realities, guided by the aegis of development, where, the considerations which one arrives at is that even if such processes took place in different periods, clearly, the transformations had causes and effects in the municipality of Belterra, over the years, without achieving the desired development processes.
Keywords: Desenvolvimento; Belterra; Borracha; Expansão Agrícola; Grãos; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS